Globin gene transcripts can utilize histone gene 3' end processing signals. - Whitelaw, E; Coates, A; Proudfoot, N (1986)
Deletion of the poly(A) site from the human alpha globin gene results in a defective gene that produces very little stable mRNA as compared to the intact gene, presumably due to the instability of the mRNA. However, if the Alpha poly(A) site is replaced by mouse histone H4 3' end processing signals, significant levels of hybrid alpha/H4 mRNA are obtained and the transcripts formed are cytoplasmic and poly(A)-. When both mouse histone 3' end processing signals and the alpha globin poly(A) site signals are placed in tandem after the alpha globin gene promoter and coding sequence, the alpha poly(A) site signals are utilized exclusively. These results show that the histone 3' end processing signals can function independently of the histone promoter and the transcripts which are normally polyadenylated (alpha globin) can be stabilized by a poly(A)- histone mRNA 3' terminus. Furthermore, these results show that the histone 3' end processing signals are less efficient than the alpha globin poly(A) site signals, if the two are placed in direct competition.